The inverse optimal value problem for linear fractional programming - Nadi, Sina; Lee, Taewoo; Prokopyev, Oleg A. (Operations research letters, 2025)
We study the inverse optimal value problem for linear fractional programming, where the goal is to find the coefficients of the fractional objective function such that the resulting optimal objective function value is as close as possible to some given target value. We show that this problem is NP-hard. Then, we provide some structural results, which are exploited to derive several reformulations and two solution algorithms. The proposed approaches are based on the Charnes-Cooper and parametric transformations.